The comprehensive effects of water-nitrogen coupling regulation on energy-saving greenhouse tomato growth and water-nitrogen utilization - Zhao, Mingyu; Niu, Dongshuang; Li, Bo; Pan, Chihai; Yao, Mingze; Mao, Lizhen; Xu, Zhanyang; Sun, Lei; Gao, Manman (Frontiers in Plant Science, 2025)
Irrigation and nitrogen application in an irrational manner can reduce tomato yield and resource use efficiency. To investigate the effects of different water and nitrogen combinations on yield, dry matter, ET, water use efficiency, and partial factor productivity of nitrogen, we conducted a tomato plot experiment from August to December in 2020 and 2021.Three irrigation levels (65%~75% θf(W1), 75%~85% θf(W2), 85%~95% θf(W3) and four nitrogen application rates 0 (N0), 120 kg·hm-2 (N1), 240 kg·hm-2 (N2), 360 kg·hm-2 (N3)) were set in this experiment. We conducted ANOVA and Pearson’s correlation analysis for a number of indicators measured in the experiment, and also utilized structural equation modeling and Entropy Weighted TOPSIS(EWTOPSIS) modeling for comprehensive analysis and evaluation. The results showed that irrigation and nitrogen application had significant effects(P<0.05) on tomato fruit yield, total dry matter content, ET and water and nitrogen utilization efficiency. Increasing irrigation and nitrogen application would achieve higher yield and total dry matter content, but was not conducive to water conservation and efficient use of water and fertilizer. Structural equation modeling indicated that ET, WUE, and dry matter all had a positive effect on yield, with WUE being the main controlling factor for yield and having the greatest influence, with a path coefficient of even 0.81. The results of the EWTOPSIS model for the two-year experiment indicators showed N1W3 as the treatment with the best overall benefits. Ultimately, this study found that greenhouse tomatoes could be optimized economically in Northeast China by controlling soil water content to 85% to 95% of field capacity and applying 120kg hm-2 of N.